Information aggregation with costly information and random ordering: Experimental evidence - Kraemer, Carlo; Nöth, Markus; Weber, Martin (Journal of economic behavior & organization, 2006)
The cost of information is an often ignored factor in economic situations, even though the information acquisition behavior of the decision makers has a crucial influence on the outcome. In this experiment, we study an information aggregation process in which subjects decide in a random sequence. Subjects observe predecessors’ decisions and can acquire additional private information at a fixed price. We analyze subjects’ information acquisition behavior and updating procedures. About one half of the individuals act rationally, whereas the other participants systematically overestimate the private signal value. This leads to excessive signal acquisitions and reduced conformity.